Exposure to intimate partner violence and lack of asthma control in adults: a cross-sectional study - Lima, Valmar Bião de; Vazquez, Vanessa Serva; Campos, Ana Clara Paixão; Santos, Letícia Marques dos; Cruz, Álvaro Augusto (São Paulo Medical Journal, 2023)
BACKGROUND: Asthma is a chronic airway disease that affects 339 million people worldwide. It is a heterogeneous disease with different risks, including in family environments, where intimate partner violence occurs. OBJECTIVE: This study aimed to investigate the possible association between psychosocial factors and asthma control in adults exposed to intimate partner violence. DESIGN AND SETTING: This cross-sectional study was conducted at a Brazilian public higher education institution in Salvador, Bahia, Brazil. METHODS: The study population consisted of adults clinically diagnosed with severe asthma and those with mild/moderate asthma identified at an asthma referral outpatient clinic. The sample comprised 492 participants who underwent clinical evaluation and completed questionnaires to assess asthma control, depression, stress, and resilience. The Conflict Tactics Scale, which measures tactics for managing marital conflicts, was used to estimate the level of intimate partner violence. RESULTS: Of the 492 participants, 76.2% were women and 91% self-referenced color black/brown, 37.8% reported low family income, 87.4% reported low education level, 71.7% reported high stress, 32.5% reported low resilience, 18.5% reported moderate or severe depression, 83.3% reported resolute negotiation, 49.4% reported major psychological aggression, 19.6% reported major physical aggression, 15.5% reported major injury, and 7.3% reported major sexual coercion. Regression analysis revealed that sex was an effect modifier. CONCLUSION: Women in situations of social vulnerability, with low income and poor education, with depression, severe asthma, and those who used aggression to resolve marital conflicts had a profile associated with a lack of asthma control.